DEMOCRACY AND DIGITAL SPHERE: SOME PROBLEMS - Popov, Nikolay; Popova, Rumyana (Revista Inclusiones, 2019)
The state is the main political organization and the primary subject or actor in the international law and international relations. The state has and executes some fundamental functions in social relations. Modern democracy is being realized in an entirely different environment comparing to the ХХth century. With the development of the Internet and digital means, public relations are also changing. This implies a new role for the democratic state in the fulfillment of its functions.